2018
DOI: 10.1016/j.compfluid.2017.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Multi-phase SPH modelling of air effect on the dynamic flooding of a damaged cabin

Abstract: The air flow may take effects on the responses of the damaged ship in the dynamic flooding process. It not only relates to the amount of inflow but also the stability of the ship. In order to accurately predict the responses of a damaged ship, it is essential to take the air into account. In this study, a multi-phase SPH model combined with a dummy boundary method is proposed. One of the advantages of the new SPH model in solving this nonlinear problem is that, it does not rely on other algorithms to track the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…In the simulation process, in order to eliminate the composite influence arising from the air compressibility, an appropriate ventilation hole is constructed on the upper deck. In [24][25][26][27], it has the side view and body lines of the ship model, and Table 1 presents the principal dimensions of the ship model [23]. The created damaged compartment is located near the bow.…”
Section: Model Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the simulation process, in order to eliminate the composite influence arising from the air compressibility, an appropriate ventilation hole is constructed on the upper deck. In [24][25][26][27], it has the side view and body lines of the ship model, and Table 1 presents the principal dimensions of the ship model [23]. The created damaged compartment is located near the bow.…”
Section: Model Descriptionmentioning
confidence: 99%
“…In the simulation process, in order to eliminate the composite influence arising from the air compressibility, an appropriate ventilation hole is constructed on the upper deck. In [24][25][26][27], it has As shown in Figure 5, two comparative damage scenarios are modeled separately. It can be found that the scenarios are specific to the location of the damage opening.…”
Section: Model Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noted that the existence of the air flow may restrain the fluid motion inside a damaged cabin 25,26 by reducing the kinematic energy of inflow water. 27 To focus on the coupling effect of the internal sloshing of the damaged cabin and the external fluid flow, the air flow and compression are not considered in this study assuming that the cabin is fully ventilated. Due to the complexity of the dynamic flooding process, the forward speed of the damaged ship is not taken into account.…”
Section: Article Scitationorg/journal/phfmentioning
confidence: 99%
“…The SPH method (an established meshless scheme) [33][34][35][36][37][38][39][40][41][42][43] is suitable for solving problems with large deformations and can easily capture a medium interface. In this method, a calculation domain is discretized into a set of particles with material properties.…”
Section: Basic Sph Equationsmentioning
confidence: 99%